Penerapan Model Pembelajaran Kooperatif Berbasis Gamifikasi untuk Meningkatkan Kemampuan Berhitung Siswa Kelas I MIN 2 Kota Palangka Raya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to (1) Describe the application of gamification-based cooperative learning models in mathematics subjects in the counting ability of grade I students. (2) To determine the students' counting ability after using gamification-based cooperative learning model in mathematics subject in grade I. (3) To find out whether there is an increase in counting ability after using a gamification-based cooperative learning model in mathematics subjects in grade I. This research used PTK which was carried out in two cycles. Each cycle includes 4 stages, namely planning, implementation, observation and reflection. The subjects of this research were students of class I B MIN 2 Kota Palangka Raya with a total of 37 students. The results showed (1) In cycle I, the analysis of teacher activity obtained a percentage of 92.70% with very good criteria, there was an increase in cycle II with a percentage of 98.80% with very good criteria. While student activity in cycle I obtained a percentage of 88.54% with very good criteria and an increase in cycle II with a percentage of 97.61% with very good criteria. (2) The increase in learning ability seen from the posttest results is evident from the increase in posttest scores in each cycle. In cycle I, the classical completeness was 56.75% to 86.48% in cycle II. (3) The increase in student learning outcomes using a gamification-based cooperative learning model to improve students' numeracy skills towards improving learning outcomes in cycle I the percentage of student completeness reached 56.75% while in cycle II it increased by 86.52%. In Cycle I N-Gain got a medium category by obtaining a value of 0.377 with the N-Gain score division category 0.3≤g≤0.7. Whereas in cycle II it got a high category of 0.755 with the N-Gain division category score g> 0.7.